The Effect of Coronavirus on Undergraduate Students in the Gauteng Province of South Africa during 2020-2022: An Interdisciplinary Assessment - Matimu Tsundzukani Nkuna; Vusimuzi Goodman Nkuna (E-Journal of Humanities, Arts and Social Sciences, 2023)
The coronavirus pandemic has affected almost every aspect of human life across the entire globe, including tertiary education. This interdisciplinary study explored how undergraduate students in tertiary institutions located in Gauteng Province of South Africa experienced and coped with the effects of the pandemic between the 2020 to 2022 academic years. The article used the Rites of Passage Concept to interpret how they transitioned from in-person learning to online learning, and from the latter to hybrid learning. It then used psychological concepts of self-efficacy, self-regulation and self-control to illustrate how they motivated themselves to continue pursuing their academic studies. To conduct this phenomenological study, the researchers used participatory observation and in-depth interviews to collect data over a three-year period. They then employed concepts from anthropology and psychology to interpret the students’ experience. While recognizing its limited scope, the researchers argued that the study was able to illustrate the symbiotic relationship between anthropology and psychology in social scientific research. It is their hope that the findings of this study contribute to existing scholarship in the field of humanities concerning stressors and coping strategies.